Modeling and characterization of fiber-reinforced (FRP) plastic honeycomb sandwich panels for bridge deck (Journal of Civil Engineering Researchers, 2023)
Several factors and reasons, including correcting errors in bridge design and construction, preventing damage caused by natural and environmental factors, forces caused by earthquakes, or strengthening the bridge structure to withstand more loads, increase the need to strengthen the bridge. Reinforcement is usually applied to a specific element in the bridge, such as the foundation, column, beam head and deck, each of which may be reinforced. Also, from the economic point of view, retrofitting of bridges is generally preferred compared to the replacement and renovation option. Bridges play an important role in rescue operations after an earthquake. It is necessary that these structures have a higher level of protection against seismic attacks. The earthquake identified the weak points of the structure. Bridges are very vulnerable to these attacks due to their low degree of uncertainty. Seismic displacements based on the principles of elastic design are much less than what the structure experiences in a real earthquake. One of the consequences is the falling of the decks due to the loss of the support surface. The decision to strengthen the bridge was made when many bending and shear cracks were created on the king beams of the bridge. The use of FRP profiles can significantly prevent losses caused by corrosion and is a good alternative to traditional methods of strengthening the structure. In this article, the design for the deck of a sandwich panel bridge reinforced with FRP fibers is presented.
Keywords: FRP; Glass fibers; Bridge decks; Pultrusion; Materials tests; Optimization